2011
DOI: 10.1007/s12032-011-9853-8
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity as a risk factor for overall survival and decision criteria for intensity of chemotherapy in elderly patients with acute myeloid leukemia

Abstract: This single-center study estimated the significance of pretreatment factors, including comorbidities, which may predict outcome in elderly patients with acute myeloid leukemia and determined how poor risk factors may be used as decision criteria for intensity of chemotherapy in this group of patients. Seventy-seven patients aged ≥ 55 years treated under four different regimens were followed up 36 month. Our results suggest that the most significant predictor for poor overall survival is comorbidity, as scored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 16 publications
2
17
0
10
Order By: Relevance
“…In the field of oncogeriatrics, distinguishing the frail elderly may influence subsequent decision-making. [16][17][18][19] This work was carried out to identify which demographic factors and/or which elements of the CGA allowed prediction of the risk of frailty as measured by the BQ. The only factors that have been found to act as predictors of the risk of frailty are age, marital status (unmarried) and dependence in IADL.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of oncogeriatrics, distinguishing the frail elderly may influence subsequent decision-making. [16][17][18][19] This work was carried out to identify which demographic factors and/or which elements of the CGA allowed prediction of the risk of frailty as measured by the BQ. The only factors that have been found to act as predictors of the risk of frailty are age, marital status (unmarried) and dependence in IADL.…”
Section: Discussionmentioning
confidence: 99%
“…Older AML patients often have comorbidity (18, 19, 2427). For example, a study using population data (SEER) including over 5000 adults diagnosed with AML (median age 78) showed that half had atleast one major comorbidity based on claims data(7).…”
Section: Individualizing Patient Assessment: Deconstructing Chronologmentioning
confidence: 99%
“…The most commonly used indices are the Charlson Comorbidity index (CCI) and the Hematopoietic Cell Transplantation Comorbidity Index (HCT-CI)(28, 29). Many studies of older adults with AML have shown a relationship between increased comorbidity burden (measured by CCI or HCT-CI) and worse outcomes including decreased remission rates, increased risk of 30-day mortality and worse overall survival (OS) (18, 2426, 30, 31). Several studies, however, have not shown such a clear relationship (27, 32, 33).…”
Section: Individualizing Patient Assessment: Deconstructing Chronologmentioning
confidence: 99%
“…15 Higher HCT-CI scores are associated with higher mortality. 12,[16][17][18][19] An MDACC study in 177 elderly AML patients (age 460) showed that early date rates were 3%, 11%, and 29% in patients with HCT-CI scores of 0 (n ¼ 39), 1-2 (n ¼ 53) and X3 (n ¼ 85) (Po0.001), respectively. Median OS was inversely affected by higher HCT-CI scores (median OS was 45, 31 and 19 weeks in these three groups, P ¼ 0.04).…”
Section: Induction Therapymentioning
confidence: 99%